Causal Linkage Between Inflammatory Bowel Disease and Primary Sclerosing Cholangitis: A Two-Sample Mendelian Randomization Analysis - Xie, Ying; Chen, Xuejie; Deng, Minzi; Sun, Yuhao; Wang, Xiaoyan; Chen, Jie; Yuan, Changzheng; Hesketh, Therese (Frontiers in Genetics, 2021)
Abstract Background：Observational studies suggest an association between inflammatory bowel disease (IBD) (including ulcerative colitis (UC) and Crohn’s disease (CD)) and Primary sclerosing cholangitis (PSC), but the causal association between the two diseases is still unclear. Methods：We used two-sample Mendelian randomization (MR) to estimate the causal association between IBD and PSC. We chose single nucleotide polymorphisms (SNPs) data for analysis obtained from previous genome-wide association studies (GWASs). Polymorphism, heterogeneity, and sensitivity analyses were performed for quality control. Results: We found that the causal associations between IBD (both UC and CD) and PSC were significant (e.g., IBD and PSC, Robust adjusted profile score (RAPS) OR=1.29, 95% CI 1.16~1.44, p＜0.01; UC and PSC, RAPS OR=1.40, 95% CI 1.23~1.58, p＜0.01; CD and PSC, RAPS OR=1.13, 95% CI 1.02~1.26, p=0.02). MR Egger, IVW and ML tests found heterogeneity statistically between determined IV estimates. The leave-one-out analysis also indicated the sensitivity of the SNPs (e.g., IBD and PSC, MR-Egger Q=644.30, p＜0.01; UC and PSC, MR-Egger Q=378.30, p＜0.01; UC and PSC, MR-Egger Q= 538.50, p＜0.01). Conclusion: MR analyses support the positive causal effect of IBD (including UC and CD) on PSC in a European population. We make suggestions for preventing and treating the two diseases.